Histopathological aspects of usual interstitial pneumonia in patients with systemic connective tissue diseases - Makovická, Mária; Durcová, Barbora; Vrbenská, Adela; Makovický, Peter; Michalčová, Patricie; Kráľová, Klaudia; Muri, Jozef (Histology and histopathology, 2025)
Five cases of patients with systemic connective tissue diseases (CTD) who developed connective tissue disease-associated interstitial lung disease (CTD-ILD) with progressive pulmonary fibrosis (PPF) are reported here. Unspecified ILD was diagnosed using high-resolution computed tomography (HRCT). Histologically, all cases were usual interstitial pneumonia (UIP) with findings of advanced (3/5) to diffuse (2/5) fibrosis, with a partially (4/5) to completely (1/5) formed image of a honeycomb lung. The fibrosis itself spread subpleurally and periseptally to more central parts (2/5) of the lung, around the alveolar ducts (2/5), or even without predisposition (1/5). Simultaneously, there was architectural reconstruction based on the mutual fusion of fibrosis without compression of the surrounding lung parenchyma (1/5), or with its compression (4/5). The whole process was accompanied by multifocal (1/5), dispersed (2/5), or organized inflammation in aggregates and lymphoid follicles (2/5). As a result of continuous fibroproduction and maturation of the connective tissue, the alveolar septa thickened, delimiting groups of alveoli that merged into air bullae. Few indistinctly visible (2/5), few clearly visible (1/5), multiple indistinctly visible (1/5), and multiple clearly visible (1/5) fibroblastic foci were present. Among the concomitant changes, areas of emphysema, bronchioloectasia, and bronchiectasis, as well as bronchial and vessel wall hypertrophy, and mucostasis in the alveoli and edema were observed. The differences in the histological appearance of usual interstitial pneumonia associated with systemic connective tissue diseases (CTD-UIP) versus the pattern associated with idiopathic pulmonary fibrosis (IPF-UIP) are discussed here. The main differences lie in spreading lung fibrosis, architectural lung remodeling, fibroblastic foci, and inflammatory infiltrates.
Keywords: počítačová rentgenová tomografie; Connective Tissue Diseases; Humans; lidé středního věku; Female; Aged; dospělí; Lung; intersticiální plicní nemoci; senioři; lidé; plíce; Adult; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; nemoci pojiva; Lung Diseases, Interstitial; mužské pohlaví; idiopatická plicní fibróza; Idiopathic Pulmonary Fibrosis